Alterations in plasma acylcarnitine and amino acid profiles may indicate poor nutrition during the suckling period due to maternal intake of an unbalanced diet and may predict later metabolic dysfunction - Pomar, Catalina A; Kuda, Ondrej; Kopecky, Jan; Rombaldova, Martina; Castro, Heriberto; Picó, Catalina; Sánchez, Juana; Palou, Andreu (FASEB journal, 2019)
Plasma profiles of acylcarnitines (ACs) and amino acids (AAs) may have interest as potential biomarkers. Here we analyzed plasma AC and AA profiles in 2 rat models with different metabolic programming outcomes: offspring of dams fed a cafeteria diet during lactation (O-CAF, with a thin-outside-fat-inside phenotype) and the offspring of dams with diet-induced obesity subjected to dietary normalization before gestation [offspring of postcafeteria dams (O-PCaf), nonaltered phenotype]. The purpose was to identify early variables that might indicate a propensity for a dysmetabolic state. O-CAF rats presented higher circulating levels of most of the lipid-derived ACs and higher hepatic expression of genes related to fatty acid oxidation ( Ppara and Cpt1a) than controls [offspring of control dams (O-C)]. They also exhibited an altered plasma AA profile. These differences were not observed in O-PCaf animals. A partial least squares-discriminant analysis score plot of the metabolomics data showed a clear separation between O-CAF and O-C animals. The long-chain ACs (C18, C18:1, C18:2, C16:1, and C16DC) and the AAs glycine, alanine, isoleucine, serine, and proline are the variables mainly influencing this separation. In summary, we have identified a cluster of ACs and AAs whose alterations may indicate poor nutrition during lactation due to maternal unbalanced diet intake and predict the later dysmetabolic phenotype observed in the offspring.-Pomar, C. A., Kuda, O., Kopecky, J., Rombaldova, M., Castro, H., Picó, C., Sánchez, J., Palou, A. Alterations in plasma acylcarnitine and amino acid profiles may indicate poor nutrition during the suckling period due to maternal intake of an unbalanced diet and may predict later metabolic dysfunction.
Keywords: Liver; cafeteria diet; Animals; Female; játra; perinatal nutrition; multivariační analýza; fyziologie výživy v mateřství; ženské pohlaví; Multivariate Analysis; laktace; Nutritional Status; Lipid Metabolism; kojená zvířata; těhotenství; karnitin; zpožděný efekt prenatální expozice; Models, Animal; metabolismus lipidů; metabolické nemoci; dieta; nutriční stav; Animals, Suckling; Diet; Male; early biomarkers; Prenatal Exposure Delayed Effects; Metabolic Diseases; krysa rodu Rattus; Maternal Nutritional Physiological Phenomena; postcafeteria; Amino Acids; zvířata; mužské pohlaví; Pregnancy; Lactation; aminokyseliny; Carnitine; Rats; modely u zvířat